Simulation of Impurity Diffusion in a Strained Nanowire Using Off-Lattice KMC (Communications in Computational Physics, 2007)
Kinetic Monte Carlo (KMC) is a stochastic model used to simulate crystalgrowth. However, most KMC models rely on a pre-defined lattice that neglects dislocations,lattice mismatch and strain effects. In this paper, we investigate the use of a3D off-lattice KMC algorithm. We test this method by investigating impurity diffusionin a strained FCC nanowire. While faster than a molecular dynamics simulation, themost general implementation of off-lattice KMC is much slower than a lattice-basedalgorithm. An improved procedure is achieved for weakly strained systems by precomputingapproximate saddle point locations based on unstrained lattice structures.In this way, one gives up some of the flexibility of the general method to restore someof the computational speed of lattice-based KMC. In addition to providing an alternativeapproach to nano-materials simulation, this type of simulation will be useful fortesting and calibrating methods that seek to parameterize the variation in the transitionrates for lattice-based KMC using continuum modeling.